THE INFLUENCE OF DIGITAL TIKTOK MARKETING CONTENT ON BRAND IMAGE IN KEMAIU PRODUCTS - Maghfiroh, Mutiara Lailatul; Mandasari, Virginia (Yayasan Education and Social Center, 2024)
This research aims to analyze the influence of TikTok content on the brand image of Kemaiu products. The research method involved a survey of TikTok users related to Kemaiu products. Findings show that TikTok content has a positive impact on Kemaiu's brand image, increasing consumer awareness and positive perceptions of the product. Factors such as creativity, authenticity, and interaction between content and audience play a key role in building a strong brand image. Managerial implications include the importance of content-based marketing strategies to harness TikTok's potential in strengthening brand identity and consumer appeal. This research sample had 34 respondents using a sampling method, namely by using sampling with certain considerations. The results of this research show that digital TikTok content has a positive and significant effect on the brand image of Kemaiu products